Total ozone trends from 1979 to 2016 derived from five merged observational datasets - the emergence into ozone recovery - Weber, Mark; Coldewey-Egbers, Melanie; Fioletov, Vitali E.; Frith, Stacey; Wild, Jeanette; Burrows, John P.; Long, Craig; Loyola, Diego (Atmospheric Chemistry and Physics, 2018)
We report on updated trends using different merged datasets from satellite and groundbased observations for the time period 1979 until 2016. Trends were determined by application of a multiple linear regression (MLR) to annual mean zonal mean data. Merged datasets used are NASA MOD V8.6 and NOAA MERGE V8.6, both based upon data from the series of SBUV and SBUV-2 satellite instruments (1978–present) and the GTO (GOME-type Total Ozone) and GSG (GOME-SCIAMACHY-GOME2) merged datasets (1995–present) that are mainly composed of satellite data from GOME, SCIAMACHY, and GOME-2A. The fifth dataset are the monthly mean zonal mean data from ground data collected at WOUDC (World Ozone and UV Data Center). The addition of four more years of data since the last WMO Ozone Assessment (2013–2016) show that for most datasets and regions the trends since the stratospheric halogens reached maximum (~ 1996 globally and ~ 2000 in polar regions) are mostly not significantly different from zero. However, for some latitudes, in particular the southern hemisphere extratropics and northern hemisphere subtropics, several datasets show small positive trends of slightly below +1 %/decade that are barely statistically significant at the 2σ uncertainty level. In the tropics only two datasets show significant trends of +0.5 to +0.8 %/decade}, while the other show near zero trends. Positive trends since 2000 are observed over Antarctic in September, but near zero trends in October as well as in March over the Arctic. Since uncertainties due to possible drifts between the datasets as well as from the merging procedure used in the satellite datasets or due to the low sampling of ground data are not accounted for, the retrieved trends can be only considered being at the brink of becoming significant, but there are indications that we are about to emerge into the expected recovery phase. Nevertheless, the recent trends are still considerably masked by the observed large year-to-year variability in total ozone.